中俄關係對美國霸權的影響 (2012-2021) - 洪欣妤; Charlotte Hung; Hung, Charlotte (2022)
碩士 國立政治大學 國際研究英語碩士學位學程(IMPIS) 106862002 國際體係正在發生根本性轉變，美國確立的秩序正受到中俄合作夥伴的挑戰。本研究的目的是調查2012-2021年間發生的中俄合作，分析這些合作是否對美國的霸權造成影響。根據我的研究，現在下定論中俄是否會最終取代美國成為霸主還為時過早。從不同的角度來看，有證據表明北京和莫斯科作為合作夥伴對世界產生了影響。從政治和經濟發展的角度來看，與美國提倡明確的意識形態不同，中俄不提倡專制。相反，他們試圖利用經濟影響力來維護他們在世界上的主導地位。例如，兩國就建設“一帶一路”和“歐亞經濟聯盟”達成一致。儘管“一帶一路”倡議讓中國有機會成為許多發展中國家的“老大哥”，但迄今為止，還沒有明確的案例表明中俄合作開展可能對世界產生重大影響的聯合經濟項目。從經濟到軍事，目前還沒有驚天動地的事例證明中俄影響大到足以取代美國成為霸主。\r\n未來，美國似乎將繼續與俄羅斯和中國保持競爭關係。此外，中俄矛盾也是美國政府在21世紀阻止軸心國形成的籌碼。比如在烏克蘭問題上，美國可以向中國尋求合作，在南海、中印邊界問題上，可以向俄羅斯尋求合作。只要中俄能夠保持相互克制，美國就有可能繼續擔任世界領導者的角色。 The international system is undergoing a fundamental shift, the orders established by the US is being challenged by China and Russia as partners. The purpose of this study is to investigate the cooperation between China and Russia that happened between 2012-2021 and analyze whether those cooperation cause impact on the US hegemony. Based on my research it might still be too early to make a solid conclusion of whether China and Russia will eventually replace the US as the hegemon. From different perspectives there is evidence showing that Beijing and Moscow have their impacts on the world as partners. On the political and economic development perspective, unlike the US promotes a clear ideology, China and Russia don’t promote autocracy. Instead, they try to use economic influence to assert their dominance in the world. For example, the two countries agree on the construction of BRI and EAEU. Despite the fact that BRI has given China the opportunity to be the “big brother” to many developing countries, there are no clear cases of China and Russia working together on a joint economic project that could create significant impacts on the world so far. From economic to military perspective, there are no earth-shaking cases so far to prove that China and Russia’s impact are large enough to replace the US as the hegemon.\r\nIn the future, it seems that the United States will continue to maintain a competitive relationship with Russia and China. In addition, the contradiction between China ...